Pengaruh Green Marketing dan Promosi Media Sosial terhadap Keputusan Pembelian Produk Eco-Friendly di Solo Raya - Bunga Aurelia; Ratnaningrum Ratnaningrum; Heni Susilowati; Titin Hargyatni (FEB Universitas Maritim Semarang, 2024)
This research aims to determine the influence of green marketing and social media promotion on purchasing decisions in the city of Solo Raya. This research uses quantitative methods using primary data through distributing questionnaires online on the Instagram platform. The questionnaire was taken using a non-probability sampling technique with the number of samples used in the research being 100 respondents. This research uses data analysis using SmartPLS software. The results of this research show that the green marketing variable has a positive and significant influence on purchasing decisions and the social media promotion variable has a positive and significant influence on purchasing decisions.